(3JYdje GdHdZGQjI ddLejY (B:s (3eMGOKI(B-(3JYGHjQ(B-(3eUWdMGJ (B/s - (3SdGej, YeGO EHQGgjes; (3EOQjS, RjGO eUWais ((3MdH, ShQjG (B:s (3OGQ Gdbde GdYQHj,s, 1999)
(3jJfGhd GdcJGH ehVhY JYdje GddZI GdHdZGQjI hTQM eYGfjgG(B.s
(3GdfU HGddZJjf GdYQHjI hGdHdZGQjI(B.s
Keywords: (3GddZI GdHdZGQjIs -- (3JYdjes